A novel method for alumina preparation by electrotransformation AlCl3 solution under NH4Cl catalyzed and with CO2 injected conditions - Han, Xiuxiu; Liu, Yan-Mei; Yang, Li-Xin; Lu, Ying-Feng; Wang, Run-Ting; Zhang, Ting-An (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
As a refractory industrial solid waste, high-alumina fly ash is discharged into the nature in large quantities, causing serious environmental harm. The extraction of valuable components such as aluminum from high-alumina fly ash has become a research hotspot at home and abroad. In view of the shortcomings of traditional alumina extraction from high-alumina fly ash, such as long technological process, large amount of waste acid and waste alkali, serious equipment corrosion. A novel method for alumina preparation by electrotransformation AlCl3 solution under NH4Cl catalyzed and with CO2 injected conditions was proposed by Northeastern University. The process has advantages, such as short flow and no waste acid discharge. In this paper, the influence of initial NH4Cl concentration in cathodic chamber on pH of solution, phase and morphology of electrotransformation products, phase, D(50) and D(90) of roasting products, and Al recovery rate were studied. Simultaneously, it was compared with electrotransformation AlCl3 solution, electrotransformation AlCl3 solution with CO2 injected and electrotransformation AlCl3 solution under NH4Cl catalyzed and without CO2 injected conditions. The results showed that when the solution in cathodic chamber was NH4Cl with CO2 injected, with electrotransformation time extension, pH increase slowly; And the morphology of electrotransformation products were all rough and fluffy block structures. Increasing initial NH4Cl concentration can effectively improve electrotransformation products crystallization state, roasting products D(50) and D(90), and Al recovery rate.